Predictive value of NT-pro BNP on outcomes of children with ventricular septal defect surgery - Weidan Chen; Yajie Tang; Ye Lu; Li Ma; Xinxin Chen; Techang Liu (Frontiers in Cardiovascular Medicine)
BackgroundLimited study has shown whether NT-proBNP is related to the prognosis of children wth ventricular septal defect (VSD) surgery. The study was conducted to determine the predictive value of NT-proBNP on outcomes of children with VSD surgery.MethodsA total of 798 children with VSD surgery were enrolled, with NT-proBNP measured at preoperatively and 24-h postoperatively. The short- and mid-term clinical outcomes were recorded. Propensity scores (PS) was performed to acquire pre-op and post NT-proBNP 24-h PS-matched cohorts for comparisons between groups.ResultsIn the pre NT-proBNP PS-matched cohort, the higher NT pro-BNP group had longer hospitalization time and lower post-op 1-month EF value compared with low NT pro-BNP group (all P < 0.05), and there wasn't significant difference of mechanical ventilation time, cardiopulmonary bypass (CPB) time, intensive care unit (CCU) stay, and ejection fraction (EF) values of 3 month to 12 months after surgery (all P > 0.05). In the post NT-proBNP PS-matched cohort, there wasn't significant difference of mechanical ventilation time, CPB time, CCU stay, hospitalization time, and EF values of 1 month to 12 months after surgery between two groups (all P > 0.05).ConclusionsVSD children with higher pre NT-proBNP level had longer hospital stays after surgery than those with lower level. Pre NT-proBNP level had no effect on mechanical ventilation time, CPB time, ACC time and CCU stay and cardiac function after 3 months postoperatively. Post-op 24-h NT pro-BNP level wasn't associated with clinical outcomes.